The Academic Leadership of Administrators Affecting Teachers’ Learning Management under the Office of Learning Promotion in Nakhon Si Thammarat Province - Sukjan, Onuma; Chanakul, Benchaporn; Prasan, Anotai (Journal of Buddhist Education and Research (JBER), 2025)
This research aimed to study the academic leadership of school administrators, examine teachers’ learning management, investigate how administrators' academic leadership affects teachers’ learning management, and identify guidelines for developing academic leadership that influences teachers’ learning management under the Office of Learning Promotion in Nakhon Si Thammarat Province. The sample consisted of 184 participants, including school administrators and teachers. Data collection tools included questionnaires and in-depth interviews. Data were analyzed using percentage, mean, standard deviation, correlation coefficient, multiple regression analysis, and content analysis. The findings were as follows: 1. The overall academic leadership of administrators was at a high level. Among the different aspects, defining the school’s mission received the highest average score, while supervision and evaluation received the lowest. 2. Teachers’ overall learning management was also at a high level. The highest average was in creating a learning-conducive environment and atmosphere, while the lowest was in school curriculum development. 3. Administrators' academic leadership - specifically in supervision and evaluation of teaching, creating a supportive learning environment, and curriculum development - had a statistically significant effect on teachers’ learning management at the .01 level. 4. The guidelines for developing administrators' academic leadership suggested that administrators should enhance their skills in technology and innovation, build networks with other administrators to exchange experiences, support teachers in improving learning management, encourage the use of innovative teaching techniques, and promote the integration of technology and innovation in instruction to systematically improve learning quality.